Rare bird documentation form for Lesser Black-backed Gull at Trickle Slough at Spirit Lake, 1999 - Schoenewe, Lee A.et al (1999)
Rare bird documentation form for a Lesser Black-backed Gull at Trickle Slough at Spirit Lake in Dickinson County, IA on November 6, 1999. Epson - sheet feed